TMEM16F-Mediated Platelet Membrane Phospholipid Scrambling Is Critical for Hemostasis and Thrombosis but not Thromboinflammation in Mice—Brief Report. Issue 11 (November 2016) - Baig, Ayesha A.; Haining, Elizabeth J.; Geuss, Eva; Beck, Sarah; Swieringa, Frauke; Wanitchakool, Podchanart; Schuhmann, Michael K.; Stegner, David; Kunzelmann, Karl; Kleinschnitz, Christoph; Heemskerk, Johan W.M.; Braun, Attila; et al.
Abstract : Objective—: It is known that both platelets and coagulation strongly influence infarct progression after ischemic stroke, but the mechanisms and their interplay are unknown. Our aim was to assess the contribution of the procoagulant platelet surface, and thus platelet-driven thrombin generation, to the progression of thromboinflammation in the ischemic brain. Approach and Results—: We present the characterization of a novel platelet and megakaryocyte-specific TMEM16F (anoctamin 6) knockout mouse. Reflecting Scott syndrome, platelets from the knockout mouse had a significant reduction in procoagulant characteristics that altered thrombin and fibrin generation kinetics. In addition, knockout mice showed significant defects in hemostasis and arterial thrombus formation. However, infarct volumes in a model of ischemic stroke were comparable with wild-type mice. Conclusions—: Platelet TMEM16F activity contributes significantly to hemostasis and thrombosis but not cerebral thromboinflammation. These results highlight another key difference between the roles of platelets and coagulation in these processes. Abstract : Supplemental Digital Content is available in the text.